Shorter distance between the esophagus and the left atrium is associated with higher rates of esophageal thermal injury after radiofrequency ablation. (3rd June 2022) - Ishidoya, Yuki; Kwan, Eugene; Dosdall, Derek J.; Macleod, Rob S.; Navaravong, Leenhapong; Steinberg, Benjamin A.; Jared Bunch, T.; Ranjan, Ravi
Abstract: Background: Esophageal thermal injury (ETI) is a known and potentially serious complication of catheter ablation for atrial fibrillation. We intended to evaluate the distance between the esophagus and the left atrium posterior wall (LAPW) and its association with esophageal thermal injury. Methods: A retrospective analysis of 73 patients who underwent esophagogastroduodenoscopy (EGD) after LA radiofrequency catheter ablation for symptomatic atrial fibrillation and pre‐ablation magnetic resonance imaging (MRI) was used to identify the minimum distance between the inner lumen of the esophagus and the ablated atrial endocardium (pre‐ablation atrial esophageal distance; pre‐AED) and occurrence of ETI. Parameters of ablation index (AI, Visitag Surpoint) were collected in 30 patients from the CARTO3 system and compared with assess if ablation strategies and AI further impacted risk of ETI. Results: Pre‐AED was significantly larger in patients without ETI than those with ETI (5.23 ± 0.96 mm vs. 4.31 ± 0.75 mm, p < .001). Pre‐AED showed high accuracy for predicting ETI with the best cutoff value of 4.37 mm. AI was statistically comparable between Visitag lesion markers with and without associated esophageal late gadolinium enhancement (LGE) detected by postablation MRI in the low‐power long‐duration ablation group (LPLD, 25‐40 W for 10–30 s, 393.16 [308.62–408.86] vs. 406.58 [364.38–451.22], p = .16) and high‐power short‐duration group (HPSD, 50 W for 5–10 s, 336.14 [299.66–380.11] vs. 330.54 [286.21–384.71], p = .53), respectively. Conclusion: Measuring the distance between the LA and the esophagus in pre‐ablation LGE‐MRI could be helpful in predicting ETI after LAPW ablation.